Microenvironment-related predictive markers of the therapeutic effectiveness of eribulin in patients with locally advanced or metastatic breast cancer: pilot study - L. A. Tashireva; N. O. Popova; V. V. Alifanov; V. E. Goldberg; E. I. Kovalenko; E. V. Artamonova; A. G. Manikhas; D. M. Ponomarenko; N. V. Levchenko; E. I. Rossokha; S. Yu. Krasilnikova; M. A. Zafirova; et al. (Опухоли женской репродуктивной системы, 2022)
Background. Triple negative breast cancer has no specific treatment sites for chemotherapy and is unfavorable in terms of prognosis. One of the drugs widely used in this cohort of patients is eribulin, which in addition to its antimitotic effect has an effect on the tumor microenvironment. The search for biological criteria that will allow predicting the effectiveness of the drug is assumed relevant since it will help to select patients who may receive the most benefit from certain therapy regimens.Objective: identification of immunological predictors of the therapeutic effectiveness of eribulin in patients with locally advanced or metastatic triple-negative breast cancer.Materials and methods. The study included 20 patients with locally advanced and metastatic triple negative breast cancer. 50 % had a short-term response (progression-free survival <3 months) to eribulin therapy, and 50 % had a long-term response (progression-free survival >6 months). Seven-color immunofluorescence was used to determine the subpopulation composition of tumor-infiltrating lymphocytes and their PD1 expression. Image acquisition and analysis were performed using the Vectra® 3.0 system and InForm® software (Akoya Biosciences, USA).Results. It has been shown that the ratio of the number of PD1-negative to PD1-positive CD20+ B-lymphocytes less than 5.5 associated with the long-term effectiveness of eribulin in patients with locally advanced or metastatic triple negative breast cancer.Conclusion. The results showed that the ratio of the number of PD1-negative to PD1-positive CD20+ B-lymphocytes can be considered as a possible marker to predict the effectiveness of eribulin in patients with breast cancer.